2020
DOI: 10.1002/msc.1526
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and loneliness, social support and social engagement among older adults: Analysis of the Oxford Pain, Activity and Lifestyle cohort

Abstract: Background: Musculoskeletal (MSK) pain is common in older adults. Physical and psychological consequences of MSK pain have been established, but it is also important to consider the social impact. We aimed to estimate the association between MSK pain and loneliness, social support and social engagement. Methods:We used baseline data from the Oxford Pain, Activity and Lifestyle study. Participants were community-dwelling adults aged 65 years or older from across England. Participants reported demographic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Therefore, other determinants such a well-organized healthcare system, strong primary care, effective self-management, and employment, might be limited as a consequence of political, social, and cultural conditions, which are not related to purely economic development. 41 All burden metrics evaluated in this study were higher in women than in men, which is consistent with the results of previous GBD studies. 7,42 The variations observed by sex could be due to incidence varying with gender, biological differences in the disease course, or access to care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, other determinants such a well-organized healthcare system, strong primary care, effective self-management, and employment, might be limited as a consequence of political, social, and cultural conditions, which are not related to purely economic development. 41 All burden metrics evaluated in this study were higher in women than in men, which is consistent with the results of previous GBD studies. 7,42 The variations observed by sex could be due to incidence varying with gender, biological differences in the disease course, or access to care.…”
Section: Discussionsupporting
confidence: 92%
“…Economic development may only improve other MSK disorders associated with mortality, but more strategies are needed to improve disabilities related to other MSK disorders. Therefore, other determinants such a well-organized healthcare system, strong primary care, effective self-management, and employment, might be limited as a consequence of political, social, and cultural conditions, which are not related to purely economic development 41 …”
Section: Discussionmentioning
confidence: 99%
“…Interview-based research has shown that chronic pain also impacts a patient’s relatives and partners, who for example report changes in leisure activities, sleep disturbances (n=12) [ 71 ], feelings of powerlessness, alienation, and emotional distress (n=9) [ 72 ]. This can in turn impair the relationships between patients and their social networks [ 72 ], thus increasing pain symptoms [ 73 ]. It is therefore important to understand when and how pain affects the social environment and vice versa.…”
Section: Pain and Social Contact In Daily Lifementioning
confidence: 99%
“…It can serve as a coping mechanism, enhance the ability to cope with pain, and facilitate pain management [ 1 , 24 ]. Insufficient and absent social support and social integration have been related to increases in pain [ 73 , 82 ] and even emerged as antecedents or magnifiers of chronic pain [ 83 , 84 ]. Contrasting these pain-buffering effects of social contact, some findings imply the pain-enhancing effects of social contact and support.…”
Section: Pain and Social Support: An Ambiguous Relationshipmentioning
confidence: 99%
“…In orthopaedic circles and further areas concerned with musculoskeletal care, loneliness is mostly discussed in the context of diseases: self-perceived loneliness and rheumatoid arthritis [52], the beneficial changes in social isolation and loneliness after total hip arthroplasty and total knee arthroplasty [53] or the inner connection between loneliness and musculoskeletal pain in older adults [54]. In short: musculoskeletal pain increases the risk of loneliness [55], particularly in the older generation.…”
Section: Lonelinessmentioning
confidence: 99%